Health benefits of fermented foods - Şanlier, Nevin; Gökcen, Büşra Başar; Sezgin, Aybüke Ceyhun (Critical reviews in food science and nutrition, 2019)
In the past, the beneficial effects of fermented foods on health were unknown, and so people primarily used fermentation to preserve foods, enhance shelf life, and improve flavour. Fermented foods became an important part of the diet in many cultures, and over time fermentation has been associated with many health benefits. Because of this, the fermentation process and the resulting fermented products have recently attracted scientific interest. In addition, microorganisms contributing to the fermentation process have recently been associated with many health benefits, and so these microorganisms have become another focus of attention. Lactic acid bacteria (LAB) have been some of the most studied microorganisms. During fermentation, these bacteria synthesize vitamins and minerals, produce biologically active peptides with enzymes such as proteinase and peptidase, and remove some non-nutrients. Compounds known as biologically active peptides, which are produced by the bacteria responsible for fermentation, are also well known for their health benefits. Among these peptides, conjugated linoleic acids (CLA) have a blood pressure lowering effect, exopolysaccharides exhibit prebiotic properties, bacteriocins show anti-microbial effects, sphingolipids have anti-carcinogenic and anti-microbial properties, and bioactive peptides exhibit anti-oxidant, anti-microbial, opioid antagonist, anti-allergenic, and blood pressure lowering effects. As a result, fermented foods provide many health benefits such as anti-oxidant, anti-microbial, anti-fungal, anti-inflammatory, anti-diabetic and anti-atherosclerotic activity. However, some studies have shown no relationship between fermented foods and health benefits. Therefore, this paper aims to investigate the health effects of fermented foods.